Dampak Kenaikan Harga Bbm Dan Inflasi Terhadap Pengeluaran Rata-Rata Per Kapita Di Riau - Herman, Herman (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
The aim of this research is to see the impact of rising fuel prices and inflation on average per capita expenditure in Riau. The data source obtained was secondary data obtained from BPS Riau in figures with a time series from 2015 to 2022. Data analysis techniques used multiple linear regression, classical assumption testing, and hypothesis testing. The research results show that for the classical assumption test all independent variables have no problems (the data are suitable for use in this research). the results of multiple linear regression obtained Y=-5,154+1689,456BBM-25,156,816Infalsi. and the results of the t test showed that variable X1 had a significant effect on the dependent variable, while variable X2 had no significant effect on the dependent variable. Meanwhile, the results of the F test showed that all independent variables had a significant effect on the dependent variable and the magnitude of the effect was 73.0 percent.